Biopsychosocial Rehabilitation of Children with Type 1 Diabetes Mellitus - Ojovan, Vitalina (International Journal of Child Health and Nutrition, 2026)
Background: The relevance of this study is determined by the need to develop an effective model of rehabilitation for children with type 1 diabetes mellitus (T1DM), considering medical, psychological, and social factors in the context of increasing chronic morbidity among the paediatric population. The purpose of the study is to substantiate the applicability of the biopsychosocial approach within the rehabilitation system for children with T1DM. Methods: Within a multidimensional review of the literature, approaches to the comprehensive evaluation of the functional state of children with T1DM are synthesised, encompassing clinical and laboratory indicators, psychological and emotional aspects of adaptation, and social determinants. Findings: It is established that the effectiveness of biological rehabilitation depends on the combination of individualised insulin therapy, nutritional regimen modification, physical activity, and the correction of oxidative stress. The psychological and emotional component includes identifying emotional difficulties, particularly during adolescence, and implementing psychoeducational and psychotherapeutic interventions to facilitate the stabilisation of behavioural responses. Institutional support and interdisciplinary cooperation ensure the application of an individualised approach in clinical practice. Conclusion: The implementation of the biopsychosocial approach enables comprehensive attention to the needs of children with T1DM, adapts rehabilitation pathways to the social environment, and improves the quality of care during long-term follow-up. The practical value of the study lies in developing a foundation for enhancing multidisciplinary paediatric endocrinology programmes that can be adapted within healthcare systems.